Inducible and reversible Clock gene expression in brain using the tTA system for the study of circadian behavior. - Hee-Kyung Hong; Jason L Chong; Weimin Song; Eun Joo Song; Amira A Jyawook; Andrew C Schook; Caroline H Ko; Joseph S Takahashi (PLoS Genetics)
The mechanism of circadian oscillations in mammals is cell autonomous and is generated by a set of genes that form a transcriptional autoregulatory feedback loop. While these "clock genes" are well conserved among animals, their specific functions remain to be fully understood and their roles in central versus peripheral circadian oscillators remain to be defined. We utilized the in vivo inducible tetracycline-controlled transactivator (tTA) system to regulate Clock gene expression conditionally in a tissue-specific and temporally controlled manner. Through the use of Secretogranin II to drive tTA expression, suprachiasmatic nucleus- and brain-directed expression of a tetO::Clock(Delta19) dominant-negative transgene lengthened the period of circadian locomotor rhythms in mice, whereas overexpression of a tetO::Clock(wt) wild-type transgene shortened the period. Low doses (10 mug/ml) of doxycycline (Dox) in the drinking water efficiently inactivated the tTA protein to silence the tetO transgenes and caused the circadian periodicity to return to a wild-type state. Importantly, low, but not high, doses of Dox were completely reversible and led to a rapid reactivation of the tetO transgenes. The rapid time course of tTA-regulated transgene expression demonstrates that the CLOCK protein is an excellent indicator for the kinetics of Dox-dependent induction/repression in the brain. Interestingly, the daily readout of circadian period in this system provides a real-time readout of the tTA transactivation state in vivo. In summary, the tTA system can manipulate circadian clock gene expression in a tissue-specific, conditional, and reversible manner in the central nervous system. The specific methods developed here should have general applicability for the study of brain and behavior in the mouse.